Caayguara, a new genus of huntsman spiders from the Brazilian Atlantic Forest (Araneae: Sparassidae) - Rheims, Cristina A. (Zootaxa, 2010)
Caayguara gen. nov. is described to include Olios albus Mello-Leitão, 1918 and eleven new species, namely Caayguara pinda sp. nov., from Espírito Santo, Rio de Janeiro and São Paulo; C. juati sp. nov. and C. apiaba sp. nov., from Bahia, Minas Gerais and Espírito Santo; C. ajuba sp. nov., from Bahia and Espírito Santo; C. cupepemassu sp. nov., from Minas Gerais, Espírito Santo, Rio de Janeiro, São Paulo, Paraná and Rio Grande do Sul; C. cupepemayri sp. nov. and C. atyaia sp. nov., from Rio de Janeiro; C. itajucamussi sp. nov., C. ybytyriguara sp. nov., C. poi sp. nov. and C. catuoca sp. nov., from São Paulo. The genus seems to be restricted to the Atlantic Forest biome and can be easily distinguished from other Neotropical huntsman genera by the presence of intermarginal denticles on the chelicerae, only two pairs of spines on ventral tibiae and one lateral spine on metatarsi I–II, by the male palps with RTA arising from medial to basal retrolateral tibiae and emboli with keels and projections, and by the female vulvae with the median part of copulatory ducts expanded, forming a sac-like structure, and the posterior part with several linearly arranged lobes. In addition, Olios albus is redescribed and the female described for the first time.